Coronavirus pandemic as a reason for limitation of human rights and freedoms - G. A. Vasilevich; I. Yu. Ostapovich; E. G. Kalinina (Правоприменение, 2021)
The subject. The article analyzes the phenomenon of the COVID-19 pandemic and its impact on the human rights and freedoms. It emphasizes that some information about the corona-virus infection was available several decades ago. At the same time, the specialists unfortunately weren’t ready for the possible mutation of this virus, which has now exposed a large-scales threat to the population of the whole world.The purpose of the article is to identify the problems of the implementation of the citizens’ rights and offer proposals for improving the Russian and Belarusian legislation and the practice of its implementation in the field of combating the coronavirus infection.The methodology. The authors take into account the practice of the European Court of Hu-man Rights and the constitutional control bodies of Russia and foreign countries. They make a conclusion on the legitimacy and necessity of the taken restrictive measures. The article is based on the dialectical method, as well as at the logical, historical, systemic methods. Methods of analysis and synthesis were of particular importance. The authors have applied the functional method to research the main areas for ensuring a reasonable balance of private (individual) and public interests.The main results, scope of application. Modern constitutions, including the Russian and the Belarusian ones, contains the most important principles of the rule of law, enshrine human rights and freedoms as the highest value. Human rights and freedoms continue to be are at the epicenter of many disputes and discussions. The modern system of rights and freedoms is constantly developing; the legal status of a person receives new content as the human civilization develops and the paradigm of values changes. For example, we see how information technology and other advances affect the scope of rights and freedoms. Rights, freedoms and obligations are interconnected and interdependent. All groups of rights are currently in the field of view of international organizations. The problem of equality, the elimination of discrimination, the restoration of violated rights, the assessment of the limits of the state's invasion in human rights and freedoms continues to be relevant nowadays.The article focuses on the international and national standards for the possible restriction of rights and freedoms in order to protect the health of the population. The international law rules on human rights oblige states to take measures to protect health and provide medical assistance to those in need.Conclusions. One of the constant problems is the relationship between the rights of a particular person and the rights of other persons, group or society as a whole and the state. At the same time, the coronavirus pandemic forced the public authorities to determine the balance of the priority of human rights and freedoms or the protection of the life and health of citizens. The coronavirus pandemic is the factor that affects the content of the legal regulation of relations in the field of human rights and freedoms. The measures taken by the state affect the right to health protection, freedom of movement, the right to education, right to have sport activity, right to work, freedom of assembly and others.The article proposes to inform the population more fully about the measures taken by the state and society in this direction, about the wider use of information technologies, about the possible responsibility for non-compliance with the requirements for the use of per-sonal protective equipment and the self-isolation regime.